Diversification of Domestic Politics of the GCC Member States After the Second Gulf War - Račius, Egdūnas (Acta Orientalia Vilnensia, 2000)
This paper will concentrate on exploring how the domestic politics of the Gulf Cooperation Council (GCC) countries have been redirected and reshaped as a consequence of the Second Gulf War. Although the war affected directly only Kuwait and Saudi Arabia, it has also been experienced by other GCC member states: Bahrain, next to Saudi Arabia, was a major base of Allied forces, United Arab Emirates had sent its jet–fighters to the operations against Iraqi troops. Therefore, white Kuwait and Saudi Arabia will be the primary focus of the paper, the rest of the Persian Gulf Arab countries will receive partial attention too.